PID-CONTROLLED HUMAN DETECTION ROBOT WITH VISUAL PROCESSING ON ALPHABOT-2 - Nguyen, Hoang-Thong; Vo, Quoc-Thang; Le, Minh-Thiet; Truong, Cong-Tuan; Tran, Duy-Dat; Pham, Cong-Hoang-Anh; Cao, Huu-Tai; Lam, Gia-Bao; Truong, Hoang-Anh; Tran, Le-Bao-Luan; Nguyen, Hoang-Quang-Minh; Nguyen, Le-Hoang-Viet; Le, Thi-Hong-Lam (Asosiasi Peneliti Sriwijaya, 2025)
This paper presents a human detection and alert robot system based on the AlphaBot2 platform and Raspberry Pi. The system employs a camera with a HOG-based human detection algorithm to locate the target within the frame and uses an ultrasonic sensor to measure the distance to the person. Based on the horizontal offset between the person and the frame centre, the PID controller adjusts the speeds of two DC motors to guide the robot smoothly and steadily toward the person. When the robot reaches a predefined distance from the detected human target, a buzzer is triggered. Through experiments, the effectiveness of the image processing and PID algorithm is evaluated, and optimal parameter values are identified for the system.